Paeonol Attenuated Vascular Fibrosis Through Regulating Treg/Th17 Balance in a Gut Microbiota-Dependent Manner - Xiaoyan Shi; Xiaoyan Shi; Hanwen Huang; Hanwen Huang; Min Zhou; Min Zhou; Yarong Liu; Yarong Liu; Hongfei Wu; Hongfei Wu; Min Dai; Min Dai (Frontiers Media S.A., 2021)
Background: Paeonol (Pae) is a natural phenolic compound isolated from Cortex Moutan, which exhibits anti-atherosclerosis (AS) effects. Our previous work demonstrated that gut microbiota plays an important role during AS treatment as it affects the efficacy of Pae. However, the mechanism of Pae in protecting against vascular fibrosis as related to gut microbiota has yet to be elucidated.Objective: To investigate the antifibrosis effect of Pae on AS mice and demonstrate the underlying gut microbiota-dependent mechanism.Methods: ApoE-/- mice were fed with high-fat diet (HFD) to replicate the AS model. H&E and Masson staining were used to observe the plaque formation and collagen deposition. Short-chain fatty acid (SCFA) production was analyzed through LC-MS/MS. The frequency of immune cells in spleen was phenotyped by flow cytometry. The mRNA expression of aortic inflammatory cytokines was detected by qRT-PCR. The protein expression of LOX and fibrosis-related indicators were examined by western blot.Results: Pae restricted the development of AS and collagen deposition. Notably, the antifibrosis effect of Pae was achieved by regulating the gut microbiota. LC-MS/MS data indicated that the level of SCFAs was increased in caecum contents. Additionally, Pae administration selectively upregulated the frequency of regulatory T (Treg) cells as well as downregulated the ratio of T helper type 17 (Th17) cells in the spleen of AS mice, improving the Treg/Th17 balance. In addition, as expected, Pae intervention can significantly downregulate the levels of proinflammatory cytokines IL-1β, IL-6, TNF-α, and IL-17 in the aorta, and upregulate the levels of anti-inflammatory factor IL-10, a marker of Treg cells. Finally, Pae's intervention in the gut microbiota resulted in the restoration of the balance of Treg/Th17, which indirectly downregulated the protein expression level of LOX and fibrosis-related indicators (MMP-2/9 and collagen I/III).Conclusion: Pae attenuated vascular fibrosis in a gut microbiota-dependent manner. The underlying protective mechanism was associated with the improved Treg/Th17 balance in spleen mediated through the increased microbiota-derived SCFA production. Collectively, our results demonstrated the role of Pae as a potential gut microbiota modulator to prevent and treat AS.